A Model for Counterinsurgency Success? The Good, the Bad and the Ugly in the Struggle against the Revolutionary Armed Forces of Colombia (2003–2012) (2020)
The Colombian counterinsurgency campaign against FARC, during the years 2003–2012, was successful in significantly reducing the insurgency to its weakest condition in history. The strategy was a result of the transformation of the leadership mind-set, which motivated an understanding of counterinsurgency as a political enterprise, demanding the participation of all state institutions and officials. This all-of-government approach allowed to place military action as part of a broader strategy, in which military commanders transformed the way the struggle was understood, placing legitimacy as a center of gravity in operations. However, the latter part of the strategy, the consolidation of state institutions in remote regions of the territory, wasn’t achieved, while extrajudicial killings clouded the entire success of the strategy